Self‐assessed competence of final‐year nursing students - Renáta Zeleníková; Elena Gurková; Radana Pěrůžková; Lenka Štureková; Darja Jarošová; Satu Kajander‐Unkuri (Wiley, 2023)
Abstract Aim To examine the overall level of self‐assessed competence of final‐year nursing 'bachelors' degree students in the Czech Republic. In addition, the study aimed at the factors associated with the students' level of competence. Design A cross‐sectional observational study. Methods Data were collected with the Czech version of the Nurse Competence Scale from 274 final‐year nursing students of the bachelor's nursing program. Data were analysed using descriptive statistics and multiple regression analyses. Results Majority of the students (80.3%) assessed their level of competence as good or very good. The highest level of competence was assessed in the category of 'managing situations' (VAS mean 67.8) and 'work role' (VAS mean 67.2). Previous work experience in healthcare and successful supervisory experience had a positive association with self‐assessed competence. Students who completed clinical placement during the COVID‐19 pandemic assessed their level of competence as lower than students before the pandemic. No Patient or Public Contribution.